Dampak Buruk atas Tindak Pidana Korupsi yang Terjadi di Indonesia - Prasya Putri Ramadhani; Hudi Yusuf (Media Hukum Indonesia (MHI), 2026)
Corruption is an extraordinary crime that has wide–ranging impacts on national development. This study aims to analyze the elements of corruption as regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, the factors contributing to the rise of corruption cases, and strategies for combating them. The research employs a literature study method involving legislation, court decisions, and previous studies. The analysis shows that corruption is caused by weak integrity among officials, ineffective supervisory systems, and a permissive culture. Combating corruption requires repressive, preventive, and systemic approaches through bureaucratic reform. Corruption in Indonesia is no longer a new legal problem for the state, as corruption has existed for thousands of years in both developed and developing countries, including Indonesia. The Anti-Corruption Law stipulates that individuals who commit corruption must compensate for state losses due to the economic and social impacts inflicted on state finances. Over time, increasing prison sentences for corruptors is expected to create a deterrent effect, thereby reducing corruption crimes.